Enucleation versus Evisceration in Ocular Trauma: A Retrospective Review and Study of Current Literature. (2nd August 2013) - Zheng, Chengjie; Wu, Albert Y.
Abstract: Purpose : To compare variables and outcomes from ocular trauma leading to either enucleation or evisceration to better inform surgical decision making. Design : Retrospective chart review. Methods : We reviewed 441 patients between 2001 and 2012 presenting with ocular trauma to a Level 1 trauma center in Queens, New York; of these, there were 16 enucleations and 6 eviscerations. Retrospective chart review noted age, gender, mechanism of injury, initial and final visual acuity, time to surgery, length of follow-up, pain, degree of motility, and complications. A review of literature in the context of our study was performed. Results : 20 patients were male and 2 patients were female; average age was 44 (SD: 20.0, range 18–91). 9/16 patients were enucleated to prevent sympathetic ophthalmia, whereas only 1/5 patient was eviscerated for this indication ( p  = 0.1619). No cases of sympathetic ophthalmia were reported over an average follow-up of 316 days. Average length of follow-up varied significantly between the two groups, with an average of 370.4 days (SD: 566.9, range 0–1870) for enucleated eyes and 172.7 days (SD: 146.3, range 0–422) for eviscerated eyes ( p  = 0.42). Medpor implants were preferred in eviscerations (5/6 eviscerations), whereas hydroxyapatite implants were preferred in enucleations (10/16 enucleations, p  = 0.04). Conclusions : Surgical decision-making in ocular trauma is largely based on surgeon preference and experience, with minimal evidence in the literature to support either enucleation or evisceration. We recommend evisceration over enucleation in cases of reliable patient follow-up due to the low incidence of sympathetic ophthalmia.